SAT0178 An Outcome Survey of 40 Patients with Budd-Chiari Syndrome due to BehÇEt'S Syndrome Followed by a Single Center. (23rd January 2014) - Caglar, E.; Ugurlu, S.; Seyahi, E.; Kantarci, F.; Sonsuz, A.; Yurdakul, S.; Yazici, H.
Abstract : Background: Budd-Chiari syndrome is a rare complication of BS with a frequency of < 1 %, and carries a high mortality rate. In a previous survey out of 14 Behcet patients with BCS, 10 (60 %) had died with a mean survival of 10 months (1 ). Objectives: We assessed the outcome in a cohort of 40 BS patients with BCS diagnosed and followed by a single center between 1977 and 2012. Methods: We reviewed records of about 8000 patients with BS who were registered at the multidisciplinary clinic at Cerrahpasa Medical Faculty between July 1977 and December 2012 (study closure). We identified 40 (37 M/ 3 F) patients who were diagnosed with BCS. The outcome of 40 patients was evaluated between September and December 2012. Attempts were made to contact every patient in this cohort by telephone calls or home visits. All thus contacted were called back to the outpatient clinic for a clinical evaluation, blood tests and hepatic Doppler USG. Hepatic Doppler USG specifically analyzed hepatic veins patency, intrahepatic collateral formation, caudate lobe hypertrophy, hepatomegaly, splenomegaly, and portal vein dilatation. Survival data were assessed by Kaplan-Meier analysis. Results: A total of 40 BS patients with BCS were surveyed. The mean age of the patients at diagnosis of BS was 28.7 ± 8.6 years, and the mean age at the onset of BCS was 30.3 ± 8.5 years. A total of 35 patients received immunosuppressive treatment (cyclophophamide n= 31; azathioprine n =4) after being diagnosed with BCS. Only 2 patients had surgical interventions. One patient had percutaneous transluminal angioplasty another transjugular intrahepatic portosystemic shunting. Fifteen patients received anticoagulant treatment. Apart from this, 3 patients were treated with thrombolytic treatment which was ineffective. Additionally, 17 patients received diuretics. By the end of the study, we had the outcome information in all patients: 20 patients (19 M/1F) (50 %) had died, while the remaining 20 were alive. Of these, 17 could be re-evaluated in the clinic. Among the patients who had died, the median survival time was 8 months (IQR: 4- 54 months). The causes of mortality were mainly due to hepatic failure (n =17) (85 %). Additionally, one had died due to myocardial infarction, another due to suicide and another with unknown cause. Postmortem study was available in one patient. Mortality rate among patients diagnosed between 1977-2000 (10/15, 67 %) was somewhat higher (Log rank P= 0.75). compared to those diagnosed between 2001-2012 (10/25, 40 %), however, the difference did not reach statistical significance in the survival analysis. Final hepatic USG among 17 patients who survived showed occlusion in one ore more hepatic veins in 12, caudate lobe hypertrophy in 8, splenomegaly in 3, and portal vein dilatation in 3. It was noted that all 17 patients had multiple intrahepatic veno-venous collaterals with good drainage. Conclusions: BCS due to BS still caries serious mortality. Mortality rate perhaps tend to decrease after 2000. Formation of intrahepatic veno-venous collaterals seem to be the only factor important in the survival. References: Reference: Bayraktar Y, et al. Budd-Chiari syndrome: a common complication of Behçet's disease. Am J Gastroenterol. 1997;92:858-62. Disclosure of Interest: None Declared